Kebijakan Perlindungan Hukum Terhadap Konsumen Online Market Place Akibat Dampak Covid-19 - I Made Amertha Wiguna; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2021)
The increasing number of online marketplace users continues to increase which also leads to increased crime, on the other hand the weak legal protection regulations. The formulation of the problem raised is How does the legal protection policy for online marketplace consumers impact Covid-19? What are the legal implications of the spread of covid-19 for online marketplace consumers? This thesis research is carried out using the normative research type. The results show that legal protection for consumers in online marketplace transactions has not been effectively carried out because in the UUPK regulations, the ITE Law, the Trade Law, PP PSTE, and PP PMSE, the contents of the regulations overlap and are inconsistent. Regulations on legal protection policies that are tailored to current and future needs are needed in order to protect consumers and support the operation of online marketplace transactions. Then provide a reference for the government as a material for consideration in order to improve legal protection policy regulations related to online transactions; 1) Fixing legal protection rules, 2) In making rules, it is necessary to involve private parties, 3) The need for good coordination between government institutions, 4) Carry out online consumer dispute resolution effectively using SiPENA.